A case of herpes simplex virus reactivation after fractional ablative carbon dioxide laser to treat a burn scar. (3rd April 2019) - Zaouak, Anissa; Benmously, Rym; Hammami, Houda; Fenniche, Samy
ABSTRACT: Fractional photothermolysis was initially introduced by Manstein in 2004 .Fractional CO2 laser technology introduced has allowed physicians to obtain good cosmetic results with a lower rate of complications than non-fractionated ablative laser treatment. However, adverse effects may still occur.Reported cases of HSV infection after fractional photothermolysis are rare. A 48-year-old woman with Fitzpatrick skin type III presented with a scar in her perioral area desiring esthetic improvement of her burn scar. She didn't have a history of recurrent herpes simplex virus (HSV) infection periorally. A fractionated resurfacing laser Quadralase (Candela) was used to treat her perioral burn scar. Two sessions were performed with a month interval. Five days after the second session of laser therapy even after she took antiviral prophylaxis based on valacyclovir 500mg twice daily 24 hours before the laser session and 3 days after, she presented with a rash on the perioral area preceded by pain. Correlation of the history and the clinical presentation was consistent with HSV reactivation. Treatment was initiated with acyclovir 10mg/kg/8h administered intravenously for 10 days with a clearing of her vesicular eruption. Fractional CO2 laser is a very safe procedure when used with accepted parameters. Early recognition, close monitoring and careful wound care will prevent long term sequelae when complications occur.